Sustainable Future for Human Security Society, Cities and Governance (Springer Singapore, 2018)
This book focuses on the human and societal aspects of sustainable development. Three major perspectives are considered: governance and its influence on sustainable development; urban environments and their broader human and environmental impacts; and disaster management. Each of these elements is critical in considering the current and prospective development of societies towards a sustainable future in which human security is guaranteed. This 2-volume set discusses a wide range of topics concerning sustainability and human security in Asia, particularly South East Asia. The individual chapters have been contributed by authors from various fields, and due to the breadth of the material are separated into two thematic volumes.The set offers a valuable resource for professionals and researchers in the urban planning industry, postgraduates, policymakers, government officials and natural resources managers. In addition, it can be used in courses on Environmental Engineering, Agriculture and Forestry, Public Policy and Earth Science.